AquaLase versus NeoSoniX - A Comparison Study - Jiraskova, Nada; Rozsival, Pavel; Kadlecova, Jana; Nekolova, Jana; Pozlerova, Jana; Dubravska, Zlatica (Biomedical papers, 2007)
Aims: To compare the metrics and surgical outcome when using Infiniti AquaLase and NeoSoniX cataract removal modalities.Methods: This prospective clinical study involved 50 patients with bilateral cataracts and lens removal using AquaLase in the right eye and NeoSoniX in the left eye. Best corrected visual acuity (BCVA), endothelial cell density and pachymetry were evaluted pre- and postoperatively. Statistical analysis was performed using the Wilcoxon Signed- Rank Test.Results: Preoperative mean pachymetry was 569 extpm 31 μ in the right eye (RE) and 560 extpm 37 μ in the left eye (LE), mean endothelial cell density 2744 extpm 418 cells/mm2 (RE) and 2730 extpm 472 cells/mm2 (LE). One week after operation pachymetry was 576 extpm 52 μ (RE) and 583 extpm 72 μ (LE) and endothelial cell density 2388 extpm 586 cells/mm2 (RE) and 2463 extpm 615 cells/mm2 (LE). One month after surgery pachymetry was 556 extpm 43 μ (RE) and 559 extpm 44 μ (LE) and endothelial cell density 2368 extpm 52 cells/mm2 (RE) and 2495 extpm 548 cells/mm2 (LE). BCVA improved in all eyes and was 0.8 or better on the first postoperative day.Conclusions: Both the NeosoniX and AquaLase minimize intraoperative damage to ocular structures.
Keywords: Phacoemulsifi cation/AquaLase/Pachymetry/Endothelial cell density